THE ROLE OF INTELLECTUALS AND JUDGES IN SUSTAINING POLITICAL SLAVERY IN CONTEMPORARY NIGERIA - Nkereuwem, Ogonna Nchekwube (EBSU Journal of Social Sciences and Humanities, 2024)
The role of intellectuals and judges in the politics of their nations cannot be over-emphasised. This study examines the role of these professionals in sustaining political slavery in Nigeria. It leans on Robert and Peter’s Existentialist Conscious Consciencism (EXIC-CONSCIENCISM) model, which explains the need to be conscientiously conscious of the role to play in our professions, society, and all we do in order to ensure that what we do is for common good. Employing qualitative, systematic review and content analysis, the study relies on observation and secondary data to make an exposition of their role in sustaining political slavery. The descriptive analysis of data shows that intellectuals and judges play negative role in Nigeria’s politics, electoral processes, electioneering and elections. As a result of corruption, ethnicity and religion, most of them compromise standards and professional ethics and put in unqualified and dubious persons in elective offices. The study concludes that the implication of playing the role manifests shortly afterwards as the same politicians turn around and chastise and enslave intellectuals and judges and the masses upon assuming offices, though excluding a few intellectuals and judges, who are their makers and allies. The study recommends strict observance of professional ethics at all times and considering the well-being of all rather than that of self and a few selfish individuals alone. Only those who are competent should be given places in public offices.